A Survey on Traffic Control System for Emergency Vehicle Clearance - Dave, Jashvant; Panchal, Shailesh (International Journal of Computer Sciences and Engineering, 2019)
Traffic congestion during peak hours is a critical issue worldwide. Due to increasing number of private vehicles, traffic jams primarily near cross roads results into significant delay in emergency services. Current surveys suggest that lives of many patients can be saved if emergency medical services could reach in time. With the evolution in sensor and communication technology, it is now possible to provide optimal solution to the problem of delay happening due to traffic related issues. Many researchers have proposed solutions for reducing delays and providing timely emergency services. Suggested solutions range from giving signaling priority to emergency vehicles to establishing a dedicated network to track the position of the emergency vehicle and ensuring an open rout to the destination. In this paper, we explore various mechanisms proposed for effective evacuation of vehicles creating traffic on the rout of emergency vehicle. The objective here is to provide clear view and state of the work done in the said area. This helps a researcher to easily understand and extend the capabilities of mechanisms according to the need.